THE IMPACT OF THE CHANGE IN THE ACCOUNTING SYSTEMS OF THE IRAQI MUNICIPAL INSTITUTIONS, KARBALA MUNICIPALITY INSTITUTION AS A MODEL - Kanar Jassim Mohammed; Prof. Dr. Sabiha Barzan Farhoud (Scholar Express Journals, 2022)
The unified accounting system is the prevailing system in all state institutions, and most of the private sector institutions. The main objective of establishing this system was to link the accounts of the economic unit with the national accounts, and this means that the system’s goal is to provide accounting information to one user who is the state with its various organs. Neglectingthe needs of other users of accounting information about economic units, as the registration system, accounting processes and legal regulations necessary to implement this system, and therefore the research aims to demonstrate the legal and accounting frameworks for accounting systems in the Iraqi environment, identify the community and the research sample, and indicate the reality of external control reports in the research sample for the period (2012-2019), which relates to the period of change from the decentralized accounting system to the unified accounting system for municipalities. The research has reached the most important conclusions, which are when applying the unified accounting system for the society and the study sample, we will face difficulties such as changing the tab related to keeping records,which differ from the records kept in the government accounting system, and the difficulties related to the development of some accounts that are characterized by privacy and branching from the main tab and the most important of those The accounts (sanitary landfills, social capital, operating capital) as well as the accounts in the unified accounting system and with them serve the objectives and activities of municipal departments, and the automated accounting system until 31/12/2019 still suffers from problems in data entry and restrictions, and the manual system was adopted The municipality did not deal with these problems with the Federal Financial Supervision Bureau and provided us with trial balances, professor cards and main records without any problems, as these problems and obstacles were limited to (7) points (the most important of which is the appearance of total amounts in some statements in the automated system in the form of boxes because there is no space for those The amounts, as well as when closing the previous fiscal year, the opening entry in the automated system does not match the entry that appears in the manual system......etc .)
Keywords: Unified accounting system; municipal institutions; external control notes